Hubungan Anemia Dengan Hipotermia Pada Neonatus Di RSUD Dr. Moewardi - . Ardiningsih; Dwi Hidayah; Endang Sutisna Sulaeman (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background: Based on data from Departemen Kesehatan Republik Indonesia (2007), one of the causes of death in the first 24 hours of life is hypothermia. Hypothermia is caused by the reduction of heat production. The production of heat in of neonates are strongly associated with the supply of oxygen. Anemia is bodys condition with haemoglobin levels below normal score according to age and gender. The oxygen supply to tissues is reduced if haemoglobin level is decreased, causing the reduction of heat production. The aim of this research is to know about the association between anemia and hypothermia on neonates. Methods: This is an observational analytic research with cross sectional design. This research was done in RSUD Dr.Moewardi. The samples were the neonates who were treated in the High Care Unit (HCU) of neonates in RSUD Dr.Moewardi on the 3rd until 15th of March 2013. Dependent variable was hypothermia, and the independent variable was anemia. The neonates haemoglobin levels were measured then the neonates temperature were observerd every 3 hours for 24 jam. The data were analyzed using fisher test, because the requirements of chi-square test were not met. Result: The results from fisher test were p = 0,225. Conclusion: The analysis showed there was not association between anemia and hypothermia in this research. Keyword: anemia, hypothermia, neonates